A COMPARATIVE STUDY OF ELECTRICITY GENERATION FROM INDUSTRIAL WASTEWATER THROUGH MICROBIAL FUEL CELL - M.I.N, Ma'arof; Girma, T. Chala; M.B., Chaudhry; B.K., Premakumar (UTP Press, 2020)
The present study presents a comparison of the electricity generation from industrial wastewater via Microbial Fuel Cell (MFC). Four experimental setups with four types of MFC were developed for this study. For MFC 1, 75% of wastewater from Factory A added to a fixed concentration of cow manure to obtain a solution of 600ml in the anodic chamber while adding distilled water into the cathodic chamber. Contrastingly, for MFC 2, 75% of wastewater from Factory A was added to a fixed concentration of cow manure to obtain a solution of 600ml in the anodic chamber, whereas distilled water mixed with 15g of potassium ferricyanide was added to the cathodic chamber. For MFC 3, a similar setup was made as in MFC 1 though it utilizes wastewater from Factory B. MFC 4 in return replicated the setup of MFC 2, yet the wastewater was collected from Factory B. Two (2) tests were conducted where Test 1 was to compare the voltage readings from MFC 1 and MFC 3, while Test 2 was for MFC 2 and MFC 4. It was observed that the voltage produced by the wastewater from Factory A was higher than that of voltage produced from Factory B by 41% in test 1 and 82.4% in test 2. Interestingly, the addition of potassium ferricyanide further increased the voltage by 63.17% when comparing between MFCs 4 and 3, while 111% for MFCs 2 and 1, respectively. Hence, it can be deduced that the addition of an external electron acceptor such as the potassium ferricyanide greatly increases the voltage produced. For future studies, other types of external electron acceptors could be tested in identifying its potential in improving the capability of the MFC. Keywords: microbial fuel cell, natural mixes, isoelectronic microbes, ecological concern